Progress of phototherapy for osteosarcoma and application prospect of blue light photobiomodulation therapy - Yang, Jiali; Fu, Qiqi; Jiang, Hui; Li, Yinghua; Liu, Muqing (Frontiers in Oncology, 2022)
Osteosarcoma (OS) is the most common primary malignant bone tumor that mainly affects the pediatric and adolescent population, limb salvage treatment has become one of the most concerned and expected outcomes of OS patients recently. Phototherapy (PT), as a novel, non-invasive and efficient anti-tumor therapeutic approach including photodynamic therapy (PDT), photothermal therapy (PTT) and photobiomodulation therapy (PBMT), has been widely applied in superficial skin tumors research and clinical treatment. OS is the typical deep tumor, and its phototherapy research faces great limitations and challenges. Surprisingly, pulse mode LED light can effectively improve tissue penetration, reduce skin damage caused by high light intensity, and has great application potential in deep tumor research. In this review, we discussed the research progress and related molecular mechanisms of phototherapy in the treatment of OS, mainly summarized the status quo of blue light PBMT in the scientific research and clinical applications of tumor treatment, and outlooked the application prospect of pulsed blue LED light in the treatment of OS, so as to further improve clinical survival rate and prognosis of OS treatment and explore corresponding cellular mechanisms.